Lesser mealworm (Alphitobius diaperinus) powder as a novel baking ingredient for manufacturing high-protein, mineral-dense snacks. (May 2020) - Roncolini, Andrea; Milanović, Vesna; Aquilanti, Lucia; Cardinali, Federica; Garofalo, Cristiana; Sabbatini, Riccardo; Clementi, Francesca; Belleggia, Luca; Pasquini, Marina; Mozzon, Massimo; Foligni, Roberta; Federica Trombetta, Maria; et al.
Graphical abstract: Highlights: Protein and mineral fortification of insects-based rusks was assessed. Compared to control rusks, fortified rusks showed protein enrichment up to 99.3% Compared to control rusks, fortified rusks showed histidine enrichment up to 129.1% Compared to control rusks, fortified rusks showed Zn enrichment up to 300% Low aw of rusks allowed a stable product to be obtained. Abstract: Increasing interest in consuming foods that are high in protein, vitamin, amino acid, and mineral contents is steering growth in the market for fortified snacks. The aim of the present study was to evaluate the use of lesser mealworm ( Alphitobius diaperinus ) powder (LP) (at 10 or 30% substitution for wheat flour) for the protein and mineral fortification of crunchy snacks (rusks). Hence, the technological, microbiological, nutritional, and sensory characteristics of the fortified rusks were evaluated. The protein content was enriched up to 99.3% in rusks with 30% substitution; moreover, a notable increase in the essential amino acids content was observed, with histidine fortification reaching up to 129.1% in rusks with 30% substitution. The incorporation of LP has led to an enrichment of almost all the minerals considered here, and especially Fe, P and Zn, with Zn showing fortification percentages of up to 300% in rusks with 30% substitution for LP. The experimental rusks showed pleasant sensory traits and low aw values. In view of the potential industrial manufacturing of insect-based rusks, the proposed product can be assigned to level 4 (validation in a laboratory environment) of the Technology Readiness Level (TRL) scale, and it is thus ready to be tested in a simulated production environment.